Subclavian venoplasty: A second life to the upper limb (Indian Journal of Case Reports, 2021)
Venoplasty, a forgotten art now rescued the upper limb circulation and made the left brachial arteriovenous fistula for hemodialysis functional avoiding the long-time need of a femoral arteriovenous fistula for hemodialysis. We report a rare case of successful left subclavian venoplasty in a 43-year-old male with end-stage chronic kidney disease on alternate day hemodialysis therapy with critical chronic total occlusion of the left subclavian vein secondary to traumatic central line insertion 8 months back presenting with gross wet edema of the left upper limb with visible venous collaterals over the left neck and the left anterior chest wall. Due to acquired left subclavian stenosis, the left brachial arteriovenous fistula for hemodialysis became non-functional and the patient was on alternate day hemodialysis with right femoral arteriovenous fistula.